Managing of People at Work : a New Paradigm for the 21st Century. - Chemuturi, Murali. (River Publishers, 2019)
The organizational environment in the 21st century is not what it was in the 20th Century. It metamorphosed with bulk outsourcing and computer-based decision support tools, and easily coupled with low-cost PC hardware which has created improvements in the productivity of people, resulting in reduced numbers. Managers of today manage the results expected of the position rather than managing to get things done as it was expected. In the physical sciences, academia leads the industry while in social sciences like management, marketing and economics, industry leads academia. To bridge the knowledge gap that exists between theory and practice, two practitioners from the industry share their expertise on topics from skill retention development to a model they developed to enhance motivation and morale.